Managing controversy Developing a strategy for handling controversy and teaching controversial issues in schools - Collective; Collective (Council of Europe, 2017)
A tool for school leaders and senior managers for handling controversy and teaching controversial issues in schools. Controversy and controversial issues are at the centre of our democratic societies. This means that learning how to deal with such issues must also be at the heart of an effective education for democratic citizenship and human rights education (EDC/HRE). The publication aims to help strengthen the managing of controversial issues at whole-school level. This will benefit young people and also help contribute to more effective Education for Democratic Citizenship and Human Rights Education (EDC/HRE), and the protection and strengthening of our democratic societies.